Philosophy of Education: The Role of Teachers’ Scepticism Instruction to Solve Students’ Disruptive Behaviour in English Learning Activity in Smp Islam Boyolali - Handayani, Duwi; Maryadi, Maryadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Philosophy of education concern of nature aim problem and phenomenon in Education. One of the educational phenomenons in our country is teaching English as foreign language. Teachers have some of difficulties to deliver the material because of some factor.Teaching English in this digital era must be creative and innovative. As a teacher, we have to prepare an interested media to deliver English for students. The difficulties aspect to attend the class during English lesson is disruptive behavior. The example of students’ disruptive behavior in English classroom is eating in the class and talk to their friend. This behavior can disturb their friend during lesson. The aims of this study are to know the kind of disruptive behaviour during English lesson, to identify the teachers’ scepticism instruction, and to analysis the role teachers’ scepticism instruction to solve students’ disruptive behaviour. This study is descriptive qualitative method. The instrument of the data is observation during English classroom activity to know what kind of disruptive behaviour done by students and their reason why did that and how teacher solve this problem during English lesson activity. The result of this study show that some students have disruptive behaviour such us eating and talk without permission during English lesson. Most of the reason why they did that because of feel bored during classroom activity, and did not understand what the meaning of sentences. The teacher’s scepticism instruction give students interest in English lesson. The teacher use epistemological, constitutive, linguistic meaning to ask students the instruction.